Bilayer TPU films integrating pH-responsive bromocresol purple–fluorescein indicators and carvacrol/tea tree oil-loaded HKUST-1@alkaline lignin: Visualization, controlled release, and meat preservation - Liuzi Du; Xiaodong Zhai; Xinyang Han; Ke Zhang; Junjun Zhang; Xiaobo Zou; Zhihua Li; Zhikun Yang; Quancai Sun; Ye Peng; Xiaowei Huang (Food Research International, 2026)

Fusicoccane glycosides from the endophytic fungus Talaromyces sp. DC-26 - Peng Zhou; Jingwen Yu; Xueying Deng; Jinyan Cai; Wenya Feng; Junjun Liu; Qin Li; Chong Dai; Chunmei Chen; Yonghui Zhang; Hucheng Zhu (Phytochemistry, 2026)

Enhancing treatment performance for agricultural runoff in ecological ditches through synergistic effects of denitrifying phosphate-accumulating bacteria and natural/synthetic media - Yonggui Zhao; Xiaoyun Sun; Bohua Ji; Ying Peng; Jingzhi Mao; Chenyu Zeng; Rui Yang; Junjun Chang (Journal of Cleaner Production, 2026)

Enzymatically synthesized native-like guaiacyl dehydrogenation polymer as a formaldehyde-free adhesive for high-strength, water-resistant plywood - Rui Luo; Wenhao Liu; Qian Tu; Yuanpu Wang; Junjun Chen; Junxian Xie; Rong Zhang; Nianjie Feng; Peng Wang (Chemical Engineering Journal, 2026)

Compensation for the initial capacity loss in lithium-ion batteries via controlled electrolyte decomposition at cathode - Jiajia Zhu; Tingyu Zhao; Qiuyu Jia; Hexiang Lan; Longfei An; Yuqi Jiang; Aiping Jin; Weiming Wang; Luying He; Jun Xiong; Junjun Peng; Ming Li; et al. (Chemical Engineering Journal, 2026)

From single-interface LN2 fracturing to CBM stimulation: Temperature optimization and cracking mechanism - Junjun Feng; Hongqing Qiu; Peng Zhang; Wei Li; Xiaofei Liu; Yankun Ma (Fuel, 2026)

Deciphering the regulatory role of the pfs gene on biofilm formation in Lactobacillus plantarum R: Insights from transcriptome and metabolome - Xin Fan; Bo Li; Xinao Xu; Binbin Long; Zhiwen Jia; Ran Wang; Junjun Gao; Yang Chen; Mingye Peng; Mengzhou Zhou (Bioresource Technology, 2026)

Ball-milling pretreatment-driven low-temperature waste cotton fibers-based hard carbon anodes for sodium-ion batteries - Yingying Zhou; Tiantao Huang; Zixin Lv; Che Wang; Junjun Peng; Aiping Jin; Jun Xiong; Linghui Yu; Ming Li; Zhongchen Ma; Jinchao Wei; Qing Chen (Biomass and Bioenergy, 2026)

Distinct phylogenetic patterns and assembly processes of abundant and rare taxa in traditional grain vinegar fermentation ecosystem - Mingye Peng; Bo Li; Yunli Zhu; Lu Guo; Lei Deng; Zhicong Shen; Zhiwen Jia; Yang Chen; Junjun Gao; Mengzhou Zhou (International Journal of Food Microbiology, 2026)

Deep eutectic solvents driving innovation in pulping technology and upgrading of dissolving pulp: A review - Junxian Xie; Shiyun Zhu; Haitao Yang; Jun Xu; Peng Wang; Junjun Chen (Bioresource Technology, 2026)

Separation and detection of ginsenosides: Challenges, industrial implications, and developments - Anqi Liu; Junjun Zhou; Yiling Luo; Yingbo Li; Yu Yang; Zibo Meng; Lixia Zhou; Hanlei Zhang; Na Liu; Ming Hui; Dandan Zhai; Peng Li (Food Research International, 2025)

Unveiling how reconstructed molybdenum oxyanions enhances the alkaline oxygen evolution reaction - Yize Wang; Jie Han; Weiwei Bao; Taotao Ai; Junjun Zhang; Zhifeng Deng; Peng Jiang (Chemical Engineering Journal, 2025)

Harnessing FDA-approved dipyridamole to inhibit NLRP3 inflammasome and improve outcomes of acute lung injury in sepsis - Xiuhui Chen; Yutong Zheng; Xiaofeng Zhang; Anran Zheng; Junjun Huang; Guoliang Deng; Xuna Wu; Yuying Peng; Xiaoling Zhang; Renshan Chen; Qing Xiao; Weijun Ye (Toxicology and Applied Pharmacology, 2025)

Effects of norfloxacin on the interaction between duckweed and its growth-promoting bacterial assemblages - Hong Lin; Junjun Chang; Tianning Liang; Chen Yang; Yingying Wei; Wei Peng; Ankun Xu; Changqun Duan; Yonggui Zhao (Journal of Hazardous Materials, 2025)

Evolutionary repeatability of chromatin accessibility in the hippocampus between echolocating bats and soft-furred tree mice - Luye Shi; Yuanshuo Ma; Qinyang Hua; Junjun Hao; Qin Zhang; Yaxin Ye; Lu Yang; Qi Liu; Peng Chen; Zhen Liu; Peng Shi (Science China Life Sciences, 2025)

NiVFe-LDH nanosheets reinforced MoS2 heterogeneous interface design for glycol-assisted water electrolysis - Suzhao Yang; Jie Han; Weiwei Bao; Taotao Ai; Xueling Wei; Peng Jiang; Zhifeng Deng; Junjun Zhang (Fuel, 2025)

Incartrilactones A and B: Two schinortriterpenoids with a 14,15-seco-15,17-cyclolancifoartane skeleton from Schisandra incarnata - Ying Gao; Juan Chen; Junjun Liu; Zijian Huang; Xiaogang Peng; Wanpeng Li; Chunlun Qin; Hanli Ruan (Phytochemistry, 2025)

Bromodomain and extraterminal domain (BET) promote autophagy in buffalo sertoli cells - Yuan Yang; Junjun Zhang; Yue Zhang; Qinqiang Sun; Ruixin Liu; Chunrong Xu; Peng Xu; Yangqing Lu; Qiang Fu (Theriogenology, 2025)

Laser-induced ZnxMnOx-rGO-C@LIG materials doped with diesel distillate for Zn-ion hybrid supercapacitors - Yuxia Wang; Hu Zou; Zhong Qi; Siyu Yang; Wenlong Jiang; Rui Zhang; Zhengchun Yang; Junjun Shi; Jie He; Peng Pan; Huayi Li (Chemical Engineering Journal, 2025)

Molecular insights into the binding mechanism of strontium and cesium on phyllosilicates with different expandability - Junjun Hou; Xiaolan Zhao; Qi Tan; Peng Wang; Xinyi Shi; Qiaohui Fan; Duoqiang Pan; Wangsuo Wu (Science of The Total Environment, 2024)

Enhanced remediation of real agricultural runoff in surface-flow constructed wetlands by coupling composite substrate-packed bio-balls, submerged plants and functional bacteria: Performance and mechanisms - Shengjiong Deng; Deshou Cun; Rufeng Lin; Dongliang Peng; Yanduo Du; Aoxue Wang; Bowen Guan; Rong Tan; Junjun Chang (Environmental Research, 2024)

Effects of bed pumice content on lahar erosion: An example from Changbaishan volcano, China - Shengwu Qin; Jiangfeng Lv; Shuangshuang Qiao; Junjun Chen; Jingyu Yao; Feng Wan; Shuaiying Peng; Gohar Rehman; Xiaowei Liu (Engineering Geology, 2024)

Modulation of evapotranspiration and stream runoff by weathered bedrock in arid and semi-arid mountains - Pengfei Lin; Peng Zhao; Jian Ma; Junjun Yang; Xi Zhu; Quanyan Tian; Jun Du; Longfei Chen; Zhibin He (Science of The Total Environment, 2024)

An observational prospective study based on a large cohort of HIV-negative neurosyphilis patients with particular reference to the Jarisch-Herxheimer reaction - Rui-Rui Peng; Juan Wu; Wei Zhao; Lin Zhu; Zhifang Guan; Xin Gu; Mei Shi; Junjun Yu; Yanchun Cheng; Pingyu Zhou (European Journal of Clinical Microbiology & Infectious Diseases, 2024)
Purpose The purpose of this study is to outline a complete picture of Jarisch-Herxheimer reaction (JHR) in the central nervous system among HIV-negative neurosyphilis patients. Methods A prospective study cohort of 772 cases with almost all stages of neurosyphilis depicted the features of JHR including occurrence rate, risk profiles, clinical manifestations, medical management and prognosis. Results The total occurrence rate of JHR was 9.3% (95% CI, 7.3-11.4%), including 4.1% (95% CI, 2.7-5.6%) with severe JHR. The reaction started 5 h after treatment initiation, peaked after 8 h, and subsided after 18 h. Patients with severe JHR experienced a longer recovery time (26 h). Patients with general paresis (OR = 6.825), ocular syphilis (OR = 3.974), pleocytosis (OR = 2.426), or a high CSF-VDRL titre (per log 2 titre increase, OR = 2.235) were more likely to experience JHR. Patients with general paresis had an 11.759-fold increased risk of severe JHR. Worsening symptoms included cognitive impairment, mania, nonsense speech, and dysphoria, while symptoms of hallucination, urination disorder, seizures, myoclonus, or aphasia appeared as new-onset symptoms. Neurosyphilis treatment did not need to be interrupted in most patients with JHR and could be reinstated in patients with seizures under supportive medication when JHR subsided. Conclusion Severe JHR displayed a 4.1% occurrence rate and clinicians should pay particular attention to patients at a higher risk of JHR. The neurosyphilis treatment regime can be restarted under intensive observation for patients with severe JHR and, if necessary, supportive medication should be initiated and continued until the end of therapy.

Dominant contribution of combustion-related ammonium during haze pollution in Beijing - Libin Wu; Peng Wang; Qiang Zhang; Hong Ren; Zongbo Shi; Wei Hu; Jing Chen; Qiaorong Xie; Linjie Li; Siyao Yue; Lianfang Wei; Linlin Song; et al. (Science Bulletin, 2024)

Magnetic resonance imaging and deoxyribonucleic acid methylation–based radiogenomic models for survival risk stratification of glioblastoma - Wentao Zhang; Zikang Yan; Jian Peng; Shan Zhao; Longke Ran; Haoyang Yin; Dong Zhong; Junjun Yang; Junyong Ye; Shengsheng Xu (Medical & Biological Engineering & Computing, 2024)

Combined treatment with pre-aeration and carrier addition strengthens the purification performance of a deep pilot-scale duckweed-based pond - Yonggui Zhao; Jinquan Li; Yuejiao Yang; Ruidong Ma; Ying Peng; Xiaoyun Sun; Siwei Gao; Junjun Chang; Changqun Duan (Journal of Water Process Engineering, 2024)

Simple and rapid photometry for measuring low dosage of periodate with bromide ion-catalyzed oxidation of ABTS - Shen Peng; Yuqin Wang; Junjun Yang; Lei Wang (Journal of Environmental Chemical Engineering, 2023)

Small molecule linoleic acid inhibiting whey syneresis via interact with milk proteins in the fermentation of set yogurt fortified with c9,t11-conjugated linoleic acid - Junjun Qing; Cheng Peng; Hongbing Chen; Haixing Li; Xiaohua Liu (Food Chemistry, 2023)

Mitochondria-associated endoplasmic reticulum membranes participate mitochondrial dysfunction and endoplasmic reticulum stress caused by copper in duck kidney - Junjun Peng; Xueyan Dai; Huiqin Fan; Chenghong Xing; Yu Zhuang; Xiaona Gao; Huabin Cao; Guoliang Hu; Fan Yang (Environmental Science and Pollution Research, 2023)

Inversion of TEM measurement data via a quantum particle swarm optimization algorithm with the elite opposition-based learning strategy - Junjun Jiao; Jiulong Cheng; Yuben Liu; Haiyan Yang; Dingrui Tan; Peng Cheng; Yuqi Zhang; Chenglin Jiang; Zhi Chen (Computers & Geosciences, 2023)

Bioimmobilization and transformation of chromium and cadmium in the fungi-microalgae symbiotic system - Junjun Wang; Qinghua Tian; Linlin Cui; Jinju Cheng; Hao Zhou; Yejuan Zhang; Anan Peng; Li Shen (Journal of Hazardous Materials, 2023)

Effects of fine ambient particulate matters on de novo hypertensive disorders of pregnancy and blood pressure before 20 weeks - Zhichao Yuan; Qin Li; Tao Su; Jie Yang; Junjun Chen; Yuanzhou Peng; Shuang Zhou; Heling Bao; Shusheng Luo; Hui Wang; Jue Liu; Na Han; et al. (Environmental Research, 2023)

Analysis on the hotspot characteristics of bird diversity distribution along the continental coastline of China - Peng Hou; Junjun Bai; Yan Chen; Jing Hou; Jiajun Zhao; Yutiao Ma; Jun Zhai (Frontiers in Marine Science, 2022)
Global climate change and disturbances from human activities lead to habitat loss and changes in habitat quality, resulting in a reduction in biodiversity. The continental coastline of China distributes some cities with highly developed economies and coastal wetlands with rich biodiversity, and both economic development and biodiversity conservation are important topics. In order to clarify the spatial distribution of bird biodiversity in coastal areas, based on the MaxEnt model and GIS spatial analysis, the distribution data of 488 species of birds and 15 environmental variables were used to simulate the suitable distribution areas of birds, and to analyze the spatial distribution and hotspots of bird biodiversity in coastal areas. The main findings of this study are as follows. (1) A total of 488 species in 249 genera of 21 orders and 81 families of birds were involved in the modeling of coastal areas. The main environmental factors affecting the potential distribution of birds in general are: land use, monthly mean diurnal temperature range, and precipitation of the driest month. (2) High value areas of bird richness are distributed in different locations in the four sea areas: In the Bohai Rim region, they are mainly distributed in the Liaohe Estuary Wetland in Liaoning Province, the vicinity of the Yongdingxin River and Haihe River in Tianjin, the eastern part of Tianjin, and the Yellow River and Yellow River Delta Wetland in Shandong Province; In the coastal area of the Yellow Sea, they are primarily found in Kunyu Mountain National Nature Reserve, Laoshan Provincial Nature Reserve in Shandong Province, and Yancheng Wetland Rare Birds National Nature Reserve in Jiangsu Province; In the coastal areas of the East China Sea, they are mainly found at the mouth of the Yangtze River, at the national nature reserve of Dongtan birds on Chongming Island, along the southeastern coast of Zhejiang Province, near the Min River and along the coast of Quanzhou in Fujian Province; In the coastal areas of the South China Sea, they are mainly distributed in the Pearl River Delta wetlands of Guangdong Province, the southeastern coastal areas of the Guangdong-Hong Kong-Macao Greater Bay Area, and the Shiwanda Mountain National Nature Reserve in Guangxi Province. (3) The spatial trends in the distribution of hotspots of birds of national priority protection in coastal areas are generally consistent, but more concentrated than the distribution of all birds. (4) After the high-value areas of bird richness were superimposed with protected areas, it was found that the intersecting area accounted for a small proportion of the protected area, and many areas near the inland had low bird richness. Finally, the findings provide references for bird biodiversity conservation and planning in coastal areas.

Fine detection on water abundance of sandstone by joint inversion of seismic and CSAMT: a case study in the western Ordos Basin, China - Yi Dong; Jiulong Cheng; Laifu Wen; Peng Cheng; Fei Li; Junjun Jiao; Qisong Huang (Acta Geophysica, 2022)

Characterization and Phylogenetic Analysis of the Complete Mitochondrial Genome of Saturnia japonica - Jiang Liu; Junjun Dai; Jinjin Jia; Yemei Zong; Yahao Sun; Ying Peng; Lei Wang; Cen Qian; Baojian Zhu; Guoqing Wei (Biochemical Genetics, 2022)

Determination of basic friction angle of three planar rock joints - Jun Peng; Zhicheng Tang; Chuanhua Xu; Di Hou; Qisong Huang; Junjun Feng (Arabian Journal of Geosciences, 2022)

An improved method used for evaluating potential environmental pollution risk based on spatial distribution and density of farms - Jianghui Wen; Bianyu Zhen; Zhenyu Pu; Xia Peng; Junjun Tan; Zhongbao Shao; Bosheng Bao; Zhiping Ran; Qishuang Gao; Bing Deng (Environmental Science and Pollution Research, 2021)

Astragaloside protects rat brain from microwave-induced functional injuries via restoring acetylcholine and normalizing electroencephalogram - Li Zhao; Yunbo Sun; Chao Yu; Junjun Chen; Xinping Xu; Xueyan Zhang; Hui Wang; Jing Zhang; Haoyu Wang; Ji Dong; Binwei Yao; Hongmei Zhou; et al. (Environmental Science and Pollution Research, 2020)

Permeability-enhanced rate model for coal permeability evolution and its application under various triaxial stress conditions - Jing Xie; Mingzhong Gao; Junjun Liu; Cong Li; Gaoyou Peng (Arabian Journal of Geosciences, 2020)

OsRhoGAP2 promoter drives inflorescence-preferential expression and confers responses to abiotic stresses in transgenic Arabidopsis - Junjun Huang; Xintian Yan; Jiajia Li; Jia Shi; Jingjing Peng; Jingyao Du; Huiwen Ge; Meina Wang; Wenjing An; Kaijie Wang; Huahua Wang; Weihong Liang (Acta Physiologiae Plantarum, 2019)

Influence of soil variability on single and competitive interaction of ammonium and potassium: experimental study on seven different soils - Poly Buragohain; S. Sreedeep; Peng Lin; Junjun Ni; Ankit Garg (Journal of Soils and Sediments, 2019)

Dual-functionality of RASSF1A overexpression in A375 cells is mediated by activation of IL-6/STAT3 regulatory loop - Mei Yi; Wei Wang; Shengnan Chen; Ya Peng; Junjun Li; Jing Cai; Ying Zhou; Qian Peng; Yuanyuan Ban; Zhaoyang Zeng; Xiaoling Li; Wei Xiong; et al. (Molecular Biology Reports, 2018)

Nitrogen Removal Performance and Enzyme Activities of Baffled Subsurface-Flow Constructed Wetlands with Macrophyte Biomass Addition - Junjun Chang; Shengjiong Deng; Wei Jia; Peng Chen; Yao Wang; Jinquan Chen (Water, Air, & Soil Pollution, 2018)

Decreased expression and activation of Stat3 in severe preeclampsia - Zhan Zhang; Xiaoqian Yang; Linlin Zhang; Zhenfeng Duan; Liting Jia; Peng Wang; Ying Shi; Ying Li; Junjun Gao (Journal of Molecular Histology, 2015)

Characterization of Sphingomonas sp. JB13 exo-inulinase: a novel detergent-, salt-, and protease-tolerant exo-inulinase - Junpei Zhou; Mozhen Peng; Rui Zhang; Junjun Li; Xianghua Tang; Bo Xu; Junmei Ding; Yajie Gao; Junrong Ren; Zunxi Huang (Extremophiles, 2015)